VIBRATION PROTECTION OF PUMPS ON THE FOUNDATION WITH A DAMPING PLATE MADE OF ELASTOMER - Mazdubay, Assylkhan; Kassenov, Assylbek; Abishev, Kairatolla; Mustafin, Adilbek; Mukanov, Ruslan; Suleimenov, Ansagan; Temirtas, Khamit (Journal of Applied Engineering Science, 2026)
This paper examines the decrease in pump efficiency under off-design operating conditions, where vibrations and dynamic loads cause bearing failures, overloading of pump–foundation connections, rotor displacement, and runout. These effects also deteriorate the performance of end and slot seals, leading to increased fluid leakage. To address this issue, the use of damping devices in the form of polyurethane elastomer plates is proposed. These materials provide high damping capacity, dynamic modulus of elasticity, tensile strength, and acoustic vibration isolation efficiency. They are also characterized by exceptional abrasion resistance, significantly exceeding that of rubber and low-carbon alloys, as well as resistance to environmental influences, water, oils, and most chemically active substances. The application of elastomer damping deviceАs significantly reduces vibration levels, decreases dynamic loads on foundations, and enhances the overall reliability of pumping equipment.